Religious Trauma in the Digital Era: A Case Study of Muslim Diaspora and the Clash of Global Traditions with Indonesian Islam - Ma’shum Ahmad; Salwa Dama Nazila; Satria Umami; Aisyah Wardatul Jannah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to analyze how religious trauma among Indonesian Muslim diasporas is produced, reproduced, and negotiated in digital spaces, and how these experiences contribute to the transformation of religious identity in a global-digital context. Beyond the experience of physical migration, Indonesian Muslim diaspora engage in ongoing religious identity negotiation through sustained exposure to digitally mediated religious norms circulating within transnational online publics. Employing a qualitative case-study approach, the research analyzes approximately 150 units of digital data collected from YouTube and TikTok between 2021–2024, including short videos, comment threads, and public interviews involving Indonesian Muslim diaspora figures. The data were examined through thematic digital discourse analysis combined with a social exegesis approach. The findings indicate that religious trauma is largely generated through digitally mediated moral judgment, the algorithmic amplification of rigid religious narratives, and the public delegitimation of individual religious choices. At the same time, digital platforms function as counter-spaces for healing, enabling narrative expression, community support, and inclusive reinterpretations of Islamic teachings. This study proposes the concept of digitally mediated religious trauma. Penelitian ini bertujuan menganalisis bagaimana trauma religius di kalangan diaspora Muslim Indonesia diproduksi, direproduksi, dan dinegosiasikan di ruang digital, serta bagaimana pengalaman tersebut berkontribusi terhadap transformasi identitas keagamaan dalam konteks global-digital. Diaspora Muslim Indonesia mengalami proses negosiasi identitas religius tidak hanya melalui pengalaman migrasi, tetapi juga melalui paparan berkelanjutan terhadap norma-norma keagamaan yang termediasi secara digital dan beredar dalam ruang publik daring transnasional. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus yang melibatkan sekitar 150 unit data digital yang dikumpulkan dari platform YouTube dan TikTok pada periode 2021–2024, meliputi video pendek, kolom komentar, dan wawancara publik yang melibatkan figur diaspora Muslim Indonesia. Analisis data dilakukan melalui analisis wacana digital tematik yang dipadukan dengan pendekatan tafsir sosial. Temuan penelitian menunjukkan bahwa trauma religius terutama dihasilkan melalui penghakiman moral yang termediasi secara digital, amplifikasi algoritmik terhadap narasi keagamaan yang rigid, serta delegitimasi publik atas pilihan keagamaan personal. Di sisi lain, platform digital juga berfungsi sebagai ruang tandingan bagi proses pemulihan melalui artikulasi naratif, dukungan komunitas, dan reinterpretasi ajaran Islam yang lebih inklusif. Penelitian ini mengajukan konsep trauma religius termediasi digital.